Modelos matemáticos de câncer e imunoterapia - Pereira, Fernanda Valim [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The incidence of neoplastic diseases shows that the search for more effective cancer treatments is still necessary. In addition to conventional treatments such as chemotherapy and radiotherapy, has been studied an alternative treatment modality called immunotherapy. We present a simple mathematical model of ordinary differential equations which includes the vascularized tumour growth under the influence of a more frequent administration with lower doses of drugs and cells of the immune system. Many scenarios are simulated with the immune system and chemotherapy showing that the tumor population can be kept at low level, but the most effective treatment is the constant immunotherapy at the same time with chemotherapy

A incidência de doenças neoplásicas mostra que a busca por tratamentos mais efetivos para o câncer ainda é necessária. Além dos tratamentos convencionais, como quimioterapia e radiote rapia, tem sido estudada uma modalidade alternativa de tratamento denominada imunoterapia. Apresentamos um modelo matemático simples de equações diferenciais ordinárias, que inclui o crescimento de tumores vascularizados sob a influência da administração de doses mais frequen tes e menores de quimioterápicos e de células do sistema imune. Muitos cenários são simulados, mostrando que a população do tumor pode ser mantida em baixo nível, demonstrado pelo o fluxo constante de células do sistema imunológico em sinergia com a quimioterapia
Keywords: Angiogenesis; Immune system; Metronomic; Tumour; Mathematical modelling; Maximum tolerated dose; Angiogênese; Sistema imunológico; Modelagem matemática; Dose máxima tolerada; Metronômico; Tumor